(untitled) (Proceedings of International Educators Conference, 2024)
The article aims to reveal the psychological mechanisms by which adolescence manifests an attitude towards one’s own health.Initially, theoretical approaches, views of a number of scientists and researchers have been analyzed in relation to the attitude towards their own health in adolescence.Also, the degree of attitude towards one’s own health in adolescence has been studied from an empirical point of view.